PERSEPSI MASYARAKAT BATAK TOBA TERHADAP PROSES MANGAIN BORU (MENGANGKAT) MARGA DALAM PERNIKAHAN ADAT BATAK TOBA DI DESA LAE PARIRA, KECAMATAN LAE PARIRA, KABUPATEN DAIRI - Sianturi, Lolanri Veronika (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
The aim of this research is to find out how the Toba Batak people perceive the process of mangain Boru (raising) the clan in Toba Batak marriages in Lae Parira Village, Lae Parira District, Dairi Regency. The method used in this study is a qualitative method, to understand what phenomena are experienced by research subjects holistically, by describing them with words and language, based on findings in the field. The results of the research show that the perception of the Toba Batak people regarding the process of mangain boru (raising) the clan in the marriage of the Toba Batak tribe is classified into two parts, where people who are mangclassified as understanding the mangain traditional tradition already know the direction and purpose of carrying out the ain tradition and know the meaning in its implementation. the mangain tradition, this can be a point of pride for the Toba Batak people as the world becomes increasingly aware of the traditional traditions of the Toba Batak people, and people who are classified as not understanding the mangain tradition This is of course a bad value for the Toba Batak community because it only symbolizes the Toba Batak community, but the lack of knowledge about the mangain tradition is caused by itself because many of the Toba Batak people follow the tradition and are unable to understand what they see, even those who follow the process